Research on Wolbachia endosymbiont (Rickettsiales: Anaplasmataceae) associated with insects in Malaysia: trends and prospects - Muhamad Azmi Mohammed,; Ameyra Aman-Zuki,; Salmah Yaakop, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2020)
Wolbachia is a gram-negative bacterium from the family Anaplasmataceae and can be found in almost 70% of arthropods. This bacterium can alter the reproductive system of its hosts through four known effects such as Cytoplasmic Incompatibility (CI), male-killing, feminization and Parthenogenesis Inducing (PI). Besides, this bacterium has also been proven to block the transmission of dengue and chikungunya viruses from its mosquito hosts to human. Due to its ability to manipulate the reproductive system of the host and block virus transmission to human, Wolbachia gains new interest to be studied. This review discusses the ascending trends and prospects of Wolbachia research in medical, entomological, and agricultural aspects in Malaysia. Wolbachia data from the first record until the current one was discussed. The positive developments and interests of Wolbachia research are reviewed for the future references of epidemiologists and agriculturists in Malaysia.